PHENOTYPIC, GENOTYPIC CHARACTERS AND NUTRITIONAL VALUE OF SEEDLESS WANI (Mangivera caesia Jack. var. Ngumpen Bali) (A Review) - I Nyoman Rai; Cokorda Gede Alit Semarajaya; Gede Wijana; I Wayan Wiraatmaja; Ngurah Gede Astawa; Ni Komang Alit Astiari (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2015)
The diversity of Mangivera caesia Jack (Balinese name: wani) in Bali was quite high. Based on the morphological characters of the fruit, 22 cultivars had been explored in the previous research (Rai et al., 2008). One of the most superior cultivar among those and very potential to be commercially developed was seedless wani (M. caesia Jack. var. Ngumpen Bali). The cultivar had specific properties that were not possessed by the others. Ninety (90) % of the total fruits produced were seedless, while the remaining (10%) has small seed. Beside that, this seedless cultivar had thick flesh, very attractive skin color (glossy yellowish green), uniformity on the size and shape of fruits, a distinctive aroma, sweet, tasty, and highly nutritious. The results of RAPD analysis of 10 wani cultivars grown in Bali showed that this seedless cultivar (Ngumpen) was grouped in to different cluster, a part from others. In comparison with 4 seeded cultivars of wani, Ngumpen cultivar had a similar nutrient content, however, it had greater fiber and a greater percentage of edible part. We concluded that the Ngumpen cultivar was a specific and unique germplasm so that should be preserved and protected.